A superhydrophobic anti-flaming coating with anti-corrosion function for paper-based triboelectric nanogenerator - Yanfang Meng; Junqing Zhao; Wenming He (Results in Chemistry)
As an effective way for energy conversion, triboelectric nanogenerators (TENGs) have aroused great attention. Particularly, the paper-based TENGs have been paid the highest emphasize for their unparalleled merits: flexibility, light weight, low cost, and recyclability under heavily allocated environmental protection. To address drawbacks of paper-based TENG (e.c. susceptible to moisture, inflammability), here, an effective superhydrophobic-flame-resistant coating for superhydrophobic and flame-resistant dual-treated paper-based TENG is, firstly, proposed. This coating was obtained by in-situ addition of fire-retardants (polyhedral methyl-silsesquioxane and ammonium polyphosphate) during the process of sol–gel reaction of two silane precursors: tetraethyl orthosilicate (TEOS) and tridecafluorooctyl triethoxysilane (FAS). This superhydrophobic-flame-resistant coating endowed paper-based TENG with excellent surfacial hydrophobicity (water contact angle above 150°) and flame-resistant properties (limit oxygen index improved by 5% compared with original sample), simultaneously. Meanwhile, the coating also exhibits outstanding anti-permeability towards water (keep WCA last more than 1 h) and resistance towards acidic corrosion. The superhydrophobic-flame-resistant modification renders the obtained TENG to work with conventional properties under humidity environment and fire protection. This paper-based TENG feasibly powers LED and alarm apparatus, demonstrating its plausibility for new approach for advanced energy harvest and conversion.